Application of Component-Based Analysis Patterns for Pattern-Based Reverse Engineering of Mobile Robot Software - Abang Jawawi, Dayang Norhayati; Deris, Safaai (Malaysian Journal of Computer Science, 2005)
Developing software for Autonomous Mobile Robot (AMR) is difficult and requires knowledge in embedded systems, real-time software issues, control theories and artificial intelligence aspects. To tackle the difficulty in developing software for AMR, many researchers have proposed the approach of reusable software component for mobile robot systems. Software pattern provides a way to reuse knowledge of expert across domain at all level of software development. In this paper component-based analysis patterns applicable to AMR software at high-level software development is proposed. Some important AMR component-based analysis patterns on AMR embedded software requirements are presented. How the analysis patterns can help in documenting two existing AMR software through pattern-based reverse engineering process is also illustrated.